Transformation of encoded GA20-oxidase gene under regulation of xylem-specific promoter CAD4 in tobacco (Nicotiana tabacum) - Hong Nhung, Nguyen; Phuong Thao, Bui; Van Doai, Nguyen; Van Phong, Nguyen; Thi Van Anh, Le; Bich Ngoc, Pham (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2S, 2017)
Overexpression of gene GA20ox encoding GA20-oxidase in plants have resulted in increasing stem elongation and improving growth rate. However, constitutive overexpression of GA20ox driven by the cauliflower mosaic virus (CaMV) 35S promoter is frequently accompanied by undesirable phenotypes such as poor rooting and small leaves. In this study, we have determined whether the expression of  gibberellin 20-oxidase (GA20-oxidase) in tobacco ( Nicotiana tabacum ) will increase stem elongation and enhance xylem formation. Transgenic binary vector pBI101 carrying GA20 gene encoding GA20-oxidase (binding c-myc tail) under the control of xylem-specific promoter CAD4 was successfully constructed and transformed into Agrobacterium tumefaciens strain C58. All the transgenic lines showed the xylem-specific expression of GA20-oxidase when using RT-PCR reaction. All 5 selected transgenic tobacco lines exhibited enhanced stem elongation compared to wild type (WT) control lines, the stem heights of transgenic lines increased from 20 to 60% than WT lines. The stem elongation ra of transgenic lines had rates of up to 1,66 folds comparing to WT. The histological staining of stem cross section showed that all the selected transgenic lines exhibit an substantial increase in xylem differentiation compared to WT, xylem widths of transgenic lines increase from 17-59% than WT. These results confimed that GA20 affected xylem differentiation and enhanced wood formation.